ANALISIS STUDI KELAYAKAN PROYEK PEMBANGUNAN WISATA PENDIDIKAN AGRO & FARMING ISLAMIC CENTRE AL HUDA, SELOGIRI - Iwan Ristanto; Satria Agung Wibawa (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2023)
Development of the Free Learning Curriculum for 2022, and the amount of public enthusiasm for the Integrated Islamic Education model has encouraged the Integrated Islamic Boarding School (PPIT), to develop formal education based on Islamic boarding schools; PAUD IT, SDIT, SMPIT, SMKIT, SMAIT which are integrated in character education through the development of an independent curriculum outside the classroom through the Short Semester Course Agro& Farming educational tour program at the Islamic Center Al Huda, Selogiri The construction of an educational tourism facility for the Agro& Farming Islamic Center Al Huda in Selogiri requires a large amount of money so a project feasibility study analysis is needed which is an important factor in a project evaluation although technical and social aspects also determine it. To carry out an economic analysis, economic benefits and costs are needed, which are then made into cash flows based on the implementation program. Calculating the value of the EIRR is assumed to be the loan service, calculating the B/C Ratio which is the difference between Benefit and Cost, and calculating the NPV value which is the difference between the profit (benefit) and cost (cost) in the conditions of average margin mudhorobah/murabahah loan services -12% average. Based on the Feasibility Study for the Development of the Agro& Farm Islamic Center Al Huda Wonogiri, it can be concluded that; the amount of EIRR = 24.0% > 12%, it is assumed that with the loan service margin being greater than 12% (current interest rate), then the project can be said to be economically viable. The B/C value = 1.932 > 1 means that if the B/C value at the loan service margin is 12% > 1, then the construction of the Agro& Farm Islamic Center Al Huda Wonogiri can be built. The difference between the profit (benefit) and cost (cost) on the condition of an average loan margin of 12% is (B-C) = IDR 723,283,139.00 > 0